Climate change impacts on socio-hydrological spaces of the Brahmaputra floodplain in Assam, Northeast India: A review - Borah, Leena; Kalita, Bedabati; Boro, Priyanka; Kulnu, Amenuo Susan; Hazarika, Nabajit (Frontiers in Water, 2022)
Intensification of the water cycle mediated by global warming increases the risk of hydrological disasters by modifying precipitation patterns across the globe which leads to adverse socio-economic impacts, especially in developing countries. Socio-hydrological spaces in the vicinity of major river systems are prone to the devastating effects of hydrological disasters yet attract human settlements due to the availability of fertile lands that support agriculture. The Brahmaputra floodplain (BFP) of Assam in Northeast India (NEI) is one such region which supports a high population in spite of being ravaged by annual floods and occasional droughts. The current work attempts to critically review the climate change impacts on socio-hydrological spaces of the BFP exploring climate change-hazard-lives and livelihood linkages of floodplain dwellers. This work utilizes peer reviewed articles along with reports of government and international/national organizations to critically appraise the following-(i) existing climate and fluvial hazard scenario in the BFP, (ii) impacts of climate change on the fluvial hazard and agriculture in the BFP and (iii) the adaptation and mitigation measures that exist in the BFP. Shifts in the long-term trends of temperature and rainfall have occurred over this region leading to speculations on future scenario of hydrological hazards and their impacts. Studies project an alteration in the hydrology and flow regime of the Brahmaputra River under climate warming scenarios which will influence the hazard characteristics with implications for agriculture and food security. Integrating disaster risk reduction with agricultural management can provide better climate resilience to the farming communities in the BFP.